Biomonitoring of Polycyclic Aromatic Hydrocarbons by Pine Needles - Levels and Trends in Southern Europe - Nuno Ratola (2013)
Polycyclic aromatic hydrocarbons (PAHs) are widespread carcinogenic and mutagenic contaminants with natural and anthropogenic sources mainly associated to combustion processes. The monitoring of these types of semi-volatile organic pollutants is a crucial step to assess their environmental exposure to organisms. Although in general this task is performed directly in their own habitat, biomonitoring offers the possibility to estimate the multi-route uptake of contaminants. Vegetation has been used for some time due to its worldwide presence, adequate uptake conditions and low availability costs. These valuable matrices allow the passive sampling of a wide range of compounds, mainly airborne. PAHs are no exception since their hydrophobic and lipophylic nature make them prone to partition into the waxy layers of plants and trees (mostly on the leaves) or, in the case of the heavier particle-bound PAHs, to be deposited in the surface. However, handling plant matrices is a complex mission to accomplish, in particular the separation of the target compounds from their lipidic structure. This led to the development of multiresidue extraction methods in the past two decades, in a demand for reliable extraction and clean-up procedures and increasingly lower limits of detection associated with enhanced chromatographic resolution. The main objective of this chapter is to present the concentrations, aromatic ring patterns and possible sources of 16 PAHs extracted from pine needles in three different countries from the South of Europe (Portugal, Spain and Greece) and try to point out potential similarities and differences in their behaviour, separating urban and non-urban areas. A total of 90 sampling sites (29 in Portugal, 34 in Spain and 27 in Greece) were selected in urban, industrial, rural and remote areas. The use of chemometric methods (namely principal component analysis-PCA) was of significant importance in the analysis and interpretation of the large environmental biomonitoring dataset produced. The PAH levels were, in general, higher in Greece, followed by Portugal and Spain, with predominance of 3-and 4-ring PAHs. Some visible differences were found in the aromatic ring patterns (and possibly in the sources) between urban and non-urban sites in the three countries. PCA further confirmed these trends, clearly separating the urban and the non-urban sites and all three countries, which suggests that the sources of contamination vary in each case and demonstrates the suitability of pine needles for trans-boundary biomonitoring of atmospheric PAHs.